Mapping amorphous SiO2 in Devonian shales and the possible link to marine productivity during incipient forest diversification - Corlett, Hilary; Feng, Jilu; Playter, Tiffany; Rivard, Benoit (My University, 2023)
Silica cycling in the world’s oceans is not straightforward to evaluate on a geological time scale. With the rise of radiolarians and sponges from the early Cambrian onward, silica can have two depositional origins, continental weathering, and biogenic silica. It is critical to have a reliable method of differentiating amorphous silica and crystalline silica to truly understand biogeochemical and inorganic silica cycling. In this study, opal-A is mapped across the Western Canada Sedimentary Basin in the Late Devonian Duvernay Formation shales using longwave hyperspectral imaging alongside geochemical proxies that differentiate between crystalline and amorphous SiO2, during the expansion of the world’s early forests. Signaled by several carbon isotope excursions in the Frasnian, the punctata Event corresponds to the expansion of forests when vascular land plants develop seeds and deeper root networks, likely resulting in increased pedogenesis. Nutrients from thicker soil horizons entering the marine realm are linked to higher levels of primary productivity in oceans and subsequent oxygen starvation in deeper waters at this time. The results of this study reveal, for the first time, the spatial distribution of amorphous SiO2 across a sedimentary basin during this major shift in the terrestrial realm when forests expand and develop deeper root networks.
Keywords: silica cycle; amorphous SiO2